Trade and geography in the economic origins of Islam: theory and evidence - Stelios Michalopoulos; Alireza Naghavi; Giovanni Prarolo (Fondazione Eni Enrico Mattei (FEEM), 2010)
This research examines the economic origins of Islam and uncovers two empirical regularities. First, Muslim countries, virtual countries and ethnic groups, exhibit highly unequal regional agricultural endowments. Second, Muslim adherence is systematically larger along the pre-Islamic trade routes in the Old World. The theory argues that this particular type of geography (i) determined the economic aspects of the religious doctrine upon which Islam was formed, and (ii) shaped its subsequent economic performance. It suggests that the unequal distribution of land endowments conferred differential gains from trade across regions, fostering predatory behavior from the poorly endowed ones. In such an environment it was mutually beneficial to institute a system of income redistribution. However, a higher propensity to save by the rich would exacerbate wealth inequality rendering redistribution unsustainable, leading to the demise of the Islamic unity. Consequently, income inequality had to remain within limits for Islam to persist. This was instituted via restrictions on physical capital accumulation. Such rules rendered the investments on public goods, through religious endowments, increasingly attractive. As a result, capital accumulation remained low and wealth inequality bounded. Geography and trade shaped the set of economically relevant religious principles of Islam affecting its economic trajectory in the preindustrial world.
Keywords: O10; O13; O16; O17; O18; F10; Z12; 330; Religion; Islam; Geography; Physical Capital; Human Capital; Land Inequality; Wealth Inequality; Trade